2015
DOI: 10.1109/jsen.2015.2460731
|View full text |Cite
|
Sign up to set email alerts
|

Twin-Core Fiber-Based Erbium-Doped Fiber Laser Sensor for Decoupling Measurement of Temperature and Strain

Abstract: In this paper, a novel all-fiber laser sensing configuration for decoupling measurement of strain and temperature based on the twin-core fiber (TCF) with an in-line embedded fiber Bragg grating (FBG) is proposed and experimentally demonstrated. An erbium doped fiber ring laser is built, with an optical signal-to-noise ratio higher than 40 dB and a power instability of 6.75 µW in 1 h. Due to the different spectrum responses of the TCF and FBG to the uniform variation of strain and temperature, the decoupling me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Kang et al [ 40 ] also noticed that reducing the cross-sensitivity between the measurands is a major problem in strain sensing. Different from the above two researchers, Kang found that little effort was made to describe the possibility of simultaneous measurement based on FRL sensors, and presented a novel laser sensing configuration for both strain and temperature in 2015.…”
Section: Sensing Applicationsmentioning
confidence: 99%
“…Kang et al [ 40 ] also noticed that reducing the cross-sensitivity between the measurands is a major problem in strain sensing. Different from the above two researchers, Kang found that little effort was made to describe the possibility of simultaneous measurement based on FRL sensors, and presented a novel laser sensing configuration for both strain and temperature in 2015.…”
Section: Sensing Applicationsmentioning
confidence: 99%
“…Several techniques such as hybrid FBG/long-period grating (LPG) [14], different diameter FBG's [15], FBG in polymer optical fiber [16], FBGs written in fibers with different levels of doping elements [17] FBGs written in single mode fiber (SMF) and twin core fiber (TCF) [18], four-core fiber combined with a FBG [19], a combination of Fabry-Perot interferometer (FPI) and FBG [20], superstructure FBG [21], coated FBG [22], FBG in Polarization Maintaining Fiber (PMF) [23], π-Phase-Shifted FBG [24], chirped FBG [25], and FBG written in PANDA fiber [26] have been proposed to solve the problem. All works are also in the goal of minimizing the complexities as well as costs of structures of the sensors [27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the flexible structure, large mode field area (Knight et al, 1998), photonic crystal fibers maintain the superior characteristics of infinite single mode (Birks et al, 1997), low loss and adjustable dispersion (Ferrando et al, 2000;Ortigosa-Blanch et al, 2000;Zhang, 2012), overcoming the defects of conventional fibers, and have replaced the traditional YAG. So far, photonic crystal fibers have great potential for applications in fiber lasers, fiber optic communication (Han, 2010), fiber optic sensing (Kang et al, 2015) and nonlinear optics (Dudley and Taylor, 2009), so researchers have extensively studied the doping of different ions in photonic crystal fibers, and thus prepared photonic crystal fiber lasers with different output characteristics.…”
Section: Introductionmentioning
confidence: 99%